Tarif Ijin Perubahan Guna Lahan Perkotaan Sebagai Bentuk Kontrol Pelaksanaan Penataan Ruang Kota - Haryo Winarso (The Institute for Research and Community Services, Institut Teknologi Bandung, 1995)
Land-use changes have been a common phenomena in Indonesian cities. Some of the changes do improve the physical as well as socio economic conditions of the areas, but, in the absence of sound legal procedure for the changes, mostly harms the environment and the people, creates traffic jam and evicts the low income people. Therefore a new legal procedure for land-use changes should be developed. This article will discuss the